Software Business. Towards Continuous Value Delivery 5th International Conference, ICSOB 2014, Paphos, Cyprus, June 16-18, 2014, Proceedings - Lassenius, Casper; Smolander, Kari (Lecture Notes in Business Information Processing,, 2014)
This book contains the refereed proceedings of the 5th International Conference on Software Business (ICSOB) held in Paphos, Cyprus, in June 2014. The theme of the event was "Shortening the Time to Market: From Short Cycle Times to Continuous Value Delivery." The 18 full papers, two short papers, two industrial papers, and two doctoral consortium abstracts accepted for ICSOB were selected from 45 submissions and are organized in sections on: strategic aspects, start-ups and software business, products and service business, software development, ecosystems, and platforms and enterprises.